The value and safety analysis of renal biopsy in patients with suspicious diagnosis of end-stage renal disease - YIN Na; TANG Mao-zhi; ZHANG Jun; HU Shuang; YU Wen-hong (Linchuang shenzangbing zazhi)
Objective To analyze the value and safety of renal biopsy in hemodialysis patients with unknown renal insufficiency,to prevent clinical misdiagnosis and to provide reference for indication of renal biopsy.Methods The clinical data of 261 patients who had been suspiciously diagnosed as end stage renal disease(ESRD)were collected from the Department of Nephrology,The first hospital affiliated of the Army medical university,Third Military Medical University from March 2006 to March 2016.According to the pathological type of renal biopsy,the patients were divided into three groups:chronic renal injury group,acute renal injury group and acute exacerbations of chronic renal injury group.The prognosis and complication were analyzed.Results One year later,our study showed that there were a total of 125 patients who entered ESRD and needed continuous renal replacement therapy,among which there were 100 cases in chronic renal injury group,2 in acute renal injury group and 23 in acute exacerbations of chronic kidney injury group.Simultaneously,a total of 136 patients had partly or completely recovered and escaped from hemodialysis after active treatment,among which there were 82 cases in acute renal injury group,and 54 were in acute exacerbations of chronic kidney injury group.There were 22 patients with complications,including 14 in chronic renal injury group,3 in acute renal injury group and 5 in acute exacerbation of chronic renal injury group.All of the complications were transient and displayed little damage to patients.Conclusions Renal biopsy in patients with unknown renal failure can better to save kidney function and avoid transition therap.It is feasible to carefully grasp the indication of renal biopsy for the patient who has higher rate of complication occurrence with chronic renal injury than that with acute renal injury.